Complementary Prognostic Value of Pelvic Magnetic Resonance Imaging and Whole-Body Fluorodeoxyglucose Positron Emission Tomography/Computed Tomography in the Pretreatment Assessment of Patients With Cervical Cancer. Issue 8 (October 2015) - Sala, Evis; Micco, Maura; Burger, Irene A.; Yakar, Derya; Kollmeier, Marisa A.; Goldman, Debra A.; Gonen, Mithat; Park, Kay J.; Abu-Rustum, Nadeem R.; Hricak, Hedvig; Vargas, Hebert Alberto
<x xml:space="preserve">Abstract</x> Objective The aim of this study was to evaluate the incremental prognostic value of pelvic magnetic resonance imaging (MRI) and whole-body 18F-fluorodeoxyglucose positron emission tomography/computed tomography (PET/CT) findings compared with clinical-histopathologic factors in patients with newly diagnosed cervical cancer. Methods The institutional review board approved this retrospective study of 114 patients (median age, 40.6 years) with International Federation of Gynecology and Obstetrics (FIGO) stage I-IVB cervical cancer who underwent pretreatment MRI and PET/CT. All scans were reviewed for locoregional tumor extent, pelvic or/and para-aortic lymphadenopathy, and distant metastases. Univariate Cox proportional hazard regression was performed to evaluate associations between clinical-histopathologic factors, imaging findings, and progression-free survival (PFS). Multivariate models were built using independent predictors for PFS. Harrell C was used to measure concordance (C index). Results Forty patients progressed within a median time of 10.4 months (range, 0.4–40.3 months). At univariate analysis, age, FIGO stage, tumor histology, tumor grade, and all MRI and PET/CT features were significantly associated with PFS (P < 0.0001 to P = 0.0474). A multivariate model including clinical and imaging parameters (parametrial invasion on MRI and para-aortic lymphadenopathy/distant metastases on PET/CT) had significantly higher concordance for predicting PFS than a model including clinical parameters only (C index: 0.81 [95% confidence interval, 0.75–0.87] vs 0.68 [95% confidence interval, 0.59–0.78]; P < 0.001). The comparison of C indices for the combined clinical and imaging model approached significance when compared with a FIGO stage model (C index: 0.81 [95% confidence interval, 0.75–0.87] vs 0.75 [95% confidence interval, 0.69–0.82]; P = 0.058). Conclusions In patients with newly diagnosed cervical cancer, a prognostic model including combined MRI and PET/CT findings provides information that complements clinical and histopathologic factors.